2013
DOI: 10.1089/jmf.2012.2577
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinus officinalisExtract SuppressesPropionibacterium acnes–Induced Inflammatory Responses

Abstract: Propionibacterium acnes is a key pathogen involved in the progression of acne inflammation. The development of a new agent possessing antimicrobial and anti-inflammatory activity against P. acnes is therefore of interest. In this study, we investigated the inhibitory effect of rosemary (Rosmarinus officinalis) extract on P. acnes-induced inflammation in vitro and in vivo. The results showed that ethanolic rosemary extract (ERE) significantly suppressed the secretion and mRNA expression of proinflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…The anti-acne effects of these medicinal plants may be involved in various distinct mechanisms, including anti-bacterial, anti-inflammatory, anti-oxidant, and anti-androgen activities (Azimi, Fallah-Tafti, Khakshur, & Abdollahi, 2012). We previously reported that plant extracts such as rosemary and wild bitter melon, and their bioactive constituents such as rosmarinic acid, phytol, lutein, and phenolic compounds suppress P. acnes-induced pro-inflammatory cytokine releases (Hsu et al, 2012;Huang et al, 2015;Tsai et al, 2013). As part of our continuing efforts to discover promising bioactive natural agents having antiacne activity, the effect of clove extract on P. acnes-induced inflammation was examined in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-acne effects of these medicinal plants may be involved in various distinct mechanisms, including anti-bacterial, anti-inflammatory, anti-oxidant, and anti-androgen activities (Azimi, Fallah-Tafti, Khakshur, & Abdollahi, 2012). We previously reported that plant extracts such as rosemary and wild bitter melon, and their bioactive constituents such as rosmarinic acid, phytol, lutein, and phenolic compounds suppress P. acnes-induced pro-inflammatory cytokine releases (Hsu et al, 2012;Huang et al, 2015;Tsai et al, 2013). As part of our continuing efforts to discover promising bioactive natural agents having antiacne activity, the effect of clove extract on P. acnes-induced inflammation was examined in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of delta-toxin production (IC 50 of 64 μg mL −1 ), a virulence factor controlled by S. aureus quorum sensing, was also detected for this extract (Quave et al, 2011). The growth inhibitory activity of rosemary extracts and essential oils against P. acnes has been reported in a number of studies (Fu et al, 2007; Weckesser et al, 2007; Tsai et al, 2013). Due to its common incorporation as an ingredient in skin and hair care ingredients, further investigation of its anti-acne activity is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…However, two of these were determined to be cytotoxic. An additional two have already been reported in the literature for their anti-acne activity (Fu et al, 2007; Weckesser et al, 2007; Coenye et al, 2012; Tsai et al, 2013). This study was the first to document the growth inhibitory activity of organic extracts of V. sativa aerial parts, V. vinifera leaves and A. microcarpus leaves.…”
Section: Discussionmentioning
confidence: 98%
“…P. acne induces the inflammation by stimulating the NF-κB (Nuclear factor kappa light chain enhancer of activated B cells) transcriptional activity in human monocytic cells which is responsible for the production of the abovementioned cytokines 38 . Additionally, in another research, they suggest that rosmarinic acid has inhibitory action against IL-8 production 39 .…”
Section: Natural Remediesmentioning
confidence: 97%